2013
DOI: 10.1038/ni.2762
|View full text |Cite
|
Sign up to set email alerts
|

A rheostat for immune responses: the unique properties of PD-1 and their advantages for clinical application

Abstract: PD-1, a negative coreceptor expressed on antigen-stimulated T cells and B cells, seems to serve as a 'rheostat' of the immune response. The molecular mechanisms of the functions of PD-1, in conjunction with the mild, chronic and strain-specific autoimmune phenotypes of PD-1-deficient mice, in contrast to the devastating fatal autoimmune disease of mice deficient in the immunomodulatory receptor CTLA-4, suggest that immunoregulation by PD-1 is rather antigen specific and is mainly cell intrinsic. Such unique pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
613
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 802 publications
(640 citation statements)
references
References 92 publications
3
613
0
3
Order By: Relevance
“…The latter also suggests that stable PD-1 expression might strictly correlate with the strength of antigen-stimulation, which is possibly lower in latent than in active chronic infections. This idea would be well in line with the concept that PD-1 serves as a rheostat following strong T-cell stimulation 61 . Moreover, several studies in active chronic infections established links between the magnitude of T-cell stimulation (or TCR avidity) and T-cell fate.…”
Section: Infections Which Show a Latent Phase (For Example Epstein-bamentioning
confidence: 54%
“…The latter also suggests that stable PD-1 expression might strictly correlate with the strength of antigen-stimulation, which is possibly lower in latent than in active chronic infections. This idea would be well in line with the concept that PD-1 serves as a rheostat following strong T-cell stimulation 61 . Moreover, several studies in active chronic infections established links between the magnitude of T-cell stimulation (or TCR avidity) and T-cell fate.…”
Section: Infections Which Show a Latent Phase (For Example Epstein-bamentioning
confidence: 54%
“…SHP-2 then interferes with various aspects of T-cell function, including proliferation and cytokine production (5). In this manner, PD-1 is thought to maintain a balance between T-cell effector function and protection against excessive damage of peripheral tissues during infection (6).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the CD56 dim subset is largely represented in PB (approximately 90%) and is characterized by high surface expression of KIRs, high cytotoxic activity against tumor-and virus-infected targets, and rapid production of cytokines on receptor-mediated cell activation. 34,35 A constitutive or inducible expression of PD-1 has been detected in different cell populations, including T, B, and myeloid cells, 14,36 whereas little is known regarding PD-1 expression on NK cells to date. In human subjects it has been reported that NK cells from patients with multiple myeloma 37 or patients with posttransplantation lymphoproliferative disorders 38 can express low PD-1 levels.…”
mentioning
confidence: 99%
“…Importantly, targeting PD-1/PD-L1 interactions can also improve the efficacy of adoptive cell therapies in tumors or chronic viral infections. [11][12][13][14] In some instances PD-1 blockade has been shown to mediate tumor eradication, [15][16][17] resulting in impressive and highly encouraging clinical results. Indeed, accumulating data indicate that the administration of an mAb to PD-1, used alone or in combination with other drugs, might provide a highly successful therapeutic tool in different types of advanced tumors, including melanoma, lung cancer, and ovarian carcinoma.…”
mentioning
confidence: 99%